The impact of political economy: on character formation, ethical education, and the communication of values in late modern pluralistic societies - Naudé, Piet; Welker, Michael; Witte, John (Evangelische Verlagsanstalt, 2023)
In our late modern pluralistic societies, there are tensions and complementarities between a plurality of individual and social claims and activities to shape societal life and a constructive pluralism of what is known as social systems. The latter provide normative codes and powers emanating from the areas of law, religion, the family, the market, the media, education, academic research, health care, defense and politics. A better understanding and steering of this complex division of powers is crucial for the common good and for freedom and peace. In this volume, a multi-disciplinary team of experts from Germany, Italy, Australia, the UK, the USA, and South Africa bring their conceptual, empirical and historical insights to bear in three broad sections: »The moral dimension of social systems«; »The interaction of religion, law and education with political systems«; and »The moral (mal)-formation evident in case studies on the global financial crisis and social media«.